9 from the Nine Worlds - Riordan, Rick (Los Angeles ; New York : Disney-Hyperion, 2018)
"Beloved characters from the Magnus Chase and the Gods of Asgard series star in these hilarious and inventive new short stories, each set in a different one of the Nine Worlds from Norse mythology"--
Keywords: Mythology, Norse -- Fiction; Short stories; Mythology, Norse -- Juvenile fiction; Short stories; Mythological fiction